Paediatric palliative home care by general paediatricians: a multimethod study on perceived barriers and incentives - Jünger, Saskia (BioMed Central, 2010)
BACKGROUND: Non-specialist palliative care, as it is delivered by general practitioners, is a basic component of a comprehensive palliative care infrastructure for adult patients with progressive and far advanced disease. Currently palliative care for children and adolescents is recognized as a distinct entity of care, requiring networks of service providers across different settings, including paediatricians working in general practice. In Germany, the medical home care for children and adolescents is to a large extent delivered by general paediatricians working in their own practice. However, these are rarely confronted with children suffering from life-limiting diseases. The aim of this study was therefore to examine potential barriers, incentives, and the professional self-image of general paediatricians with regard to paediatric palliative care. METHODS: Based on qualitative expert interviews, a questionnaire was designed and a survey among general paediatricians in their own practice (n = 293) was undertaken. The survey has been developed and performed in close cooperation with the regional professional association of paediatricians. RESULTS: The results showed a high disposition on part of the paediatricians to engage in palliative care, and the majority of respondents regarded palliative care as part of their profile. Main barriers for the implementation were time restrictions (40.7%) and financial burden (31.6%), sole responsibility without team support (31.1%), as well as formal requirements such as forms and prescriptions (26.6%). Major facilitations were support by local specialist services such as home care nursing service (83.0%), access to a specialist paediatric palliative care consultation team (82.4%), as well as an option of exchange with colleagues (60.1%). CONCLUSIONS: Altogether, the high commitment to this survey reflects the relevance of the issue for paediatricians working in general practice. Education in basic palliative care competence and communication skills was seen as an important prerequisite for the engagement in paediatric palliative home care. A local network of specialist support on site and a 24/7 on-call service are necessary in order to facilitate the implementation of basic palliative care by paediatricians in their own practice.